Culture for Sale: Unpacking Consumer Perceptions of Cultural Appropriation - Lin, Jason D; Kim, Nicole You Jeung; Uduehi, Esther; Keinan, Anat (Journal of Consumer Research, 2024)
Abstract High-profile instances of brands accused of cultural appropriation suggest that even the most prominent brands fail to fully understand the complexities of this phenomenon. This work experimentally unpacks consumer perceptions of cultural appropriation and its impact on brand attitudes and purchase interest. The authors begin by developing and validating a scale for measuring perceptions of cultural appropriation. Next, a series of studies demonstrates that viewing this phenomenon through a historical lens can help determine when and why the use of cultural elements is viewed as appropriative. Specifically, an emphasis on historical power imbalance explains why liberal consumers are more likely to recognize cultural appropriation and why commercializing disadvantaged cultures is considered appropriation, whereas using elements from advantaged cultures may be more acceptable. The conceptualization further identifies brand actions and interventions that influence perceptions of cultural appropriation, including externally emphasizing historical power imbalance, how brands obtain cultural elements, and how brands represent the culture in their product offerings and marketing. These findings help marketers (1) avoid launching products that can be damaging to the brand and offensive to consumers and (2) understand how to better promote products in a way that prevents rather than amplifies these negative perceptions.